KEY ASPECTS OF YOUTH POLICY IMPLEMENTATION IN INTERNATIONAL PRACTICE AND PROPOSED MODELS - Khalil Yusifli (International Journal of Innovative Technologies in Social Science, 2025)
As is known, youth policy has become one of the priority areas in the policies of foreign countries, especially in Western countries. The state youth policy of modern foreign countries is, in fact, a system of state priorities and measures that ensure the creation of conditions and opportunities for the successful integration of young people into society (socialization) and the effective implementation of their potential in the interests of the state. State youth policy is given much attention by both universal and regional international organizations. An important role in this area belongs to the United Nations. At the same time, this is reflected in the activities of specialized UN organizations in this area, especially UNESCO, ILO and WHO. At the regional level, the Council of Europe and the European Union pay serious attention to youth policy. The most important component of youth policy implemented by foreign countries is the legal regulation of this process. In this regard, the youth policy of individual foreign countries is implemented on the basis of program documents, legislation and legislative acts in this area. In world practice, the most common models for implementing youth policy are the American liberal (USA), European and mixed models. Each of them has both advantages and disadvantages, which makes it extremely important to take into account local specifics when applying them, as well as when preparing and implementing national programs and other documents.